2018
DOI: 10.4102/ajlm.v7i1.708
|View full text |Cite
|
Sign up to set email alerts
|

Detection of minority drug resistant mutations in Malawian HIV-1 subtype C-positive patients initiating and on first-line antiretroviral therapy

Abstract: BackgroundMinority drug resistance mutations (DRMs) that are often missed by Sanger sequencing are clinically significant, as they can cause virologic failure in individuals treated with antiretroviral therapy (ART) drugs.ObjectiveThis study aimed to estimate the prevalence of minor DRMs among patients enrolled in a Malawi HIV drug resistance monitoring survey at baseline and at one year after initiation of ART.MethodsForty-one plasma specimens collected from HIV-1 subtype C-positive patients and seven clonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 39 publications
3
13
1
Order By: Relevance
“…While the actual clinical relevance of minority DRMS remains contested [38][39][40], other studies [19,21,25,31,35] have reported association between minority variants with virologic failure. This concurs with our observation that the higher the frequency of baseline minority mutations the more the viral load count at end point (Kruskal Wallis p < 0.005) when we compared cases and controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the actual clinical relevance of minority DRMS remains contested [38][39][40], other studies [19,21,25,31,35] have reported association between minority variants with virologic failure. This concurs with our observation that the higher the frequency of baseline minority mutations the more the viral load count at end point (Kruskal Wallis p < 0.005) when we compared cases and controls.…”
Section: Discussionmentioning
confidence: 99%
“…The NGS assays have a high sensitivity and offer a platform for high-throughput sequencing, enabling NGS to detect HIV minority variants that constitute as low as 0.05-20% of the HIV viral population [13][14][15]. Minority drug-resistance mutations (DRMs) are of clinical relevance since they can cause treatment failure in individuals initiated on HIV antiretroviral drugs [16][17][18][19]. Minority variants can reduce the e cacy of HIV drugs, for example, etravirine [20] and other NNRTI-based rst-line regimens [21].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, new knowledge and disease evolution will continue to press us to change. In this issue, Zhou et al’s 7 response to the need for drug resistance information was to evaluate the application of viral population deep sequencing for people living with HIV in Malawi. They demonstrate that deep sequencing can identify drug-resistant minority variants, making informed drug choices that eliminate rather than select resistant HIV lineages possible.…”
Section: Building Resources To Meet Evolving Laboratory Medicine Chalmentioning
confidence: 99%
“…Some of the technologies that will aid laboratory contributions to better care are relatively new ones, operating on new platforms and taking advantage of what we now know about the molecular basis of disease. Zhou et al’s 7 next generation sequencing approach is a case in point. But still others will be extensions of tried and true technologies that may not require new skills and infrastructure.…”
Section: Building Resources To Meet Evolving Laboratory Medicine Chalmentioning
confidence: 99%
See 1 more Smart Citation